2014
DOI: 10.1080/14683857.2014.903598
|View full text |Cite
|
Sign up to set email alerts
|

Turkey’s foreign policy towards Bulgaria and the Turkish minority (1923–1934)

Abstract: This article sets out to study relations between Turkey and Bulgaria during the Inter-war period of 1923-1934 and its effects on the Turkish minority living in Bulgaria. In bringing international, national and community level dynamics together, it will attempt to show how the relations developed between the Republic of Turkey and Bulgaria affected the conditions of the Turkish minority. Once the diplomatic relationship was established between the two states, Ankara and Sofia made efforts to constrain deliberat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…68 Since he was also pursuing to reduce the Great Powers' influence, Rüştü bey opposed the Italian efforts to subordinate the Turkish-Greek-Bulgarian rapprochement to their interests and the expansion of the French influence over Bulgaria through its membership in the Little Entente. 69 The Legation in Athens concluded that the failed Bulgarian-Albanian initiative on the First Balkan Conference was a clear signal the moment was not ripe to move from the informal to the official negotiations. The discussion in the same format on the particular obstacles was considered as appropriate for the time being.…”
mentioning
confidence: 99%
“…68 Since he was also pursuing to reduce the Great Powers' influence, Rüştü bey opposed the Italian efforts to subordinate the Turkish-Greek-Bulgarian rapprochement to their interests and the expansion of the French influence over Bulgaria through its membership in the Little Entente. 69 The Legation in Athens concluded that the failed Bulgarian-Albanian initiative on the First Balkan Conference was a clear signal the moment was not ripe to move from the informal to the official negotiations. The discussion in the same format on the particular obstacles was considered as appropriate for the time being.…”
mentioning
confidence: 99%